(untitled) - Handlin, Oscar (Cambridge, Masachusetts, 1966)
This illusion was the product of the absence in America of the kind of differences familiar to the Old World. Europeans missed here the overt indications of rank.
Keywords: Minorities,Dân tộc thiểu số; United States,Nước Mỹ